About contravention arrests to practices of police harassment. Reflections on changes and continuities in the stereotypes of police conflictivity om the perspective of young people organized of the city of Córdoba - Plaza Schaefer, Valeria (Universidad Nacional del Litoral, 2020)
It is considered that in modern society, the exercise of police violence is an inevitable consequence of the function of reproduction of a particular social order and also, in order to fulfill that function, you need to carry out a process of selection of people who come forward as conflicting. is is what equently in criminal and criminological literature is referred to as a stereotype of criminality, but about which there is little production about its definition. erefore, first, the process of social differentiation that operates and the characteristics associated with it is analyzed, to then investigate which are the relevant brands in the application of the police conflict stereotype in a specific case, according to the view of the same addressees. e application of stereotype is analyzed om the look of young people om popular sectors organized, grouped in the Collective of Youth for Our Rights, analyzing two different moments (2003–2013 / 2015–2017), in order to investigate changes and continuities in those processes of stereotyping in the city of Córdoba.